Sphingosine Kinases and Sphingosine 1-Phosphate Receptors: Signaling and Actions in the Cardiovascular System - Cannavo, Alessandro; Liccardo, Daniela; Komici, Klara; Corbi, Graziamaria; de Lucia, Claudio; Femminella, Grazia D.; Elia, Andrea; Bencivenga, Leonardo; Ferrara, Nicola; Koch, Walter J.; Paolocci, Nazareno; Rengo, Giuseppe (Frontiers in Pharmacology, 2017)
The sphingosine kinases 1 and 2 (SphK1 and 2) catalyze the phosphorylation of the lipid, sphingosine, generating the signal transmitter, sphingosine 1-phosphate (S1P). The activation of such kinases and the subsequent S1P generation and secretion in the blood serum of mammals represent a major checkpoint in many cellular signaling cascades. In fact, activating the SphK/S1P system is critical for cell motility and proliferation, cytoskeletal organization, cell growth, survival and response to stress. In the cardiovascular system, the physiological effects of S1P intervene through the binding and activation of a family of five highly-selective G protein-coupled receptors (GPCRs), called S1PR1–5. Importantly, SphK/S1P signal is present on both vascular and myocardial cells. S1P is a well-recognized survival factor in many tissues. Therefore, it is not surprising that the last two decades have seen a flourishing of interest and investigative efforts directed to obtain additional mechanistic insights into the signaling, as well as the biological activity of this phospholipid, and of its receptors, especially in the cardiovascular system. Here, we will provide an up-to-date account on the structure and function of sphingosine kinases, discussing the generation, release, and function of S1P. Keeping the bull's eye on the cardiovascular system, we will review the structure and signaling cascades and biological actions emanating from the stimulation of different S1P receptors. We will end this article with a summary of the most recent, experimental and clinical observations targeting S1PRs and SphKs as possible new therapeutic avenues for cardiovascular disorders, such as heart failure.